Analisis Perhitungan Harga Pokok Produksi dengan Metode Job Order Costing - Sitti Muliana; Rahmi Nurainun (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
This study aims to determine the calculation of the cost of goods manufactured using the job order costing method at UD Pelita Raya, especially for door products. The data analysis method used is descriptive analysis method. The results of this study indicate that the company calculates the cost of goods manufactured has not been maximized in including the elements of cost. The cost of goods manufactured is calculated using the Job Order Costing method by including all cost elements ranging from raw material costs, labor costs and factory overhead costs in calculating the cost of production. The calculation results show a significant difference where the cost of production calculated by UD Pelita Raya is lower than the cost of production using the Job Order Costing method. The difference in the cost of production of course affects the selling price and profit and loss of UD Pelita Raya where the selling price is determined and the profit earned by UD Pelita Raya is too low, therefore it is very necessary to pay attention to the calculation of the cost of production of a company. Keywords: Cost of Production, Job Order Costing, Factory Overhead